2023
DOI: 10.1007/s11696-023-03157-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel NLRP3 inhibitors: a comprehensive approach using 2D-QSAR, molecular docking, molecular dynamics simulation and drug-likeness evaluation

Mouad Mouhsin,
Oussama Abchir,
Faiçal Sbai El Otmani
et al.

Abstract: This research, employing computational methodologies, aimed to discover potential inhibitors for the nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3), an intracellular sensor pivotal in in ammation and various disease processes. Despite NLRP3's critical role, there remains a research gap in the identi cation of novel inhibitors, making this study's objective signi cant. Through statistical techniques such as principal component analysis (PCA) and K-means clustering, data re nement and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…These compounds exhibited moderate-to-high activity against α-glucosidase, as listed in Table 8, where their IC 50 values were transformed into pIC 50 values (-logIC 50 ) for QSAR modeling. The structures of the studied compounds were generated and optimized under the MMFF94 force field by using Chem3D V. 19.0.0.22 [22]. A database containing 33 substituted 1,2,4-triazoles was retrieved from a previous study [14].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds exhibited moderate-to-high activity against α-glucosidase, as listed in Table 8, where their IC 50 values were transformed into pIC 50 values (-logIC 50 ) for QSAR modeling. The structures of the studied compounds were generated and optimized under the MMFF94 force field by using Chem3D V. 19.0.0.22 [22]. A database containing 33 substituted 1,2,4-triazoles was retrieved from a previous study [14].…”
Section: Methodsmentioning
confidence: 99%
“…Averaged and centered Moreau-Broto autocorrelation of lag 8 weighted by intrinsic state [17] VE3_Dzs Logarithmic coefficient sum of the last eigenvector from Barysz matrix weighted by Sanderson EN [18] nHsOH The count of a specific atom-type Hydrogen (H) E-State associated with hydroxy groups (OH) [19] CIC1 1-ordered complementary information content [20] RotBFrac Fraction of rotatable bonds, excluding terminal bonds [21] Pharmaceuticals 2024, 17 The results of the Y-randomization test showed that none of the random trials could match the original model, as indicated in Table 1. The lesser values for R 2 and Q 2 on each iteration, and their averages (R 2 YS = 0.195 and Q 2 YS = −0.341) suggest that the developed QSAR models are not based on random correlations.…”
Section: Aatsc8smentioning
confidence: 99%